Clinical Pharmacogenetics Implementation Consortium Guidelines for HLA‐B Genotype and Abacavir Dosing: 2014 Update. Issue 5 (21st February 2014) - Martin, M A; Hoffman, J M; Freimuth, R R; Klein, T E; Dong, B J; Pirmohamed, M; Hicks, J K; Wilkinson, M R; Haas, D W; Kroetz, D L
<x xml:space="preserve">Abstract</x> The Clinical Pharmacogenetics Implementation Consortium (CPIC) Guidelines for HLA‐B Genotype and Abacavir Dosing were originally published in April 2012. We reviewed recent literature and concluded that none of the evidence would change the therapeutic recommendations in the original guideline; therefore, the original publication remains clinically current. However, we have updated the Supplementary Material online and included additional resources for applying CPIC guidelines to the electronic health record. Up‐to‐date information can be found at PharmGKB (http://www.pharmgkb.org). Clinical Pharmacology & Therapeutics (2014); 95 5, 499–500. doi:10.1038/clpt.2014.38